Variety of Expressions of Arrogance in The Qur’an - Zaini, Muhammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The problem in this paper is the number of expressions used by the Qur'an to refer to the word arrogant, namely takabburan, marahan, 'uluwwan, 'utuwwan, ashiru, jabbāran, and mukhtālan, which are different expressions in terms of words but have the same meaning, namely arrogance. This raises the question, "What is the difference between these different expressions?" The discussion in this paper employs the tafsir mawdhu'i method, with library research, to collect verses of the Qur'an that have the same meaning in the sense that they both discuss one topic of the problem. The data used are verses of the Qur'an, books of Tafsir, the Arabic Dictionary, Mu'jam, and secondary sources in the form of books by several scholars. Furthermore, the author provides information and explanations before concluding. The results of the study of the words are that the six words in question have meanings that are almost the same as one another but with different contexts and purposes. Takabburan is the arrogance of man towards Allah by not believing and bowing down to Allah. 'Uluwwan is the arrogance of man on earth, manifested by committing injustice. 'Marahan is being arrogant while walking, or walking with pride. The word mukhtālan is the same as delusion, the feeling that one has advantages (such as wealth) over others, turning one's face and cheeks away when talking to others. The word jabbāran refers to being proud of one's parents and not being devoted to them. The phrase takabburān occurs 48 times, the phrase 'uluwwan occurs 8 times, the phrase jabbāran occurs 3 times, the phrase mukhtālan occurs 3 times, the phrase marahan occurs 2 times, and the phrase asyiru occurs 2 times.